Two-phases hybrid model for neutrals. (January 2019) - Valentinuzzi, M.; Marandet, Y.; Bufferand, H.; Ciraolo, G.; Tamain, P.
Highlights: New hybrid fluid-kinetic code for atoms developed in which atoms population is divided in two phases that can "evaporate" or "condensate" into one-another. Hybrid code coupled to plasma solver to simulate evolution of electrons, ions, molecules and atoms in realistic 2D geometry. New hybrid code shown to obtain negligible differences with respect to a fully-kinetic reference case, while improving the computational performances of the code package. Abstract: A new hybrid fluid-kinetic code for the atoms has been developed and implemented in Soledge2D. The new code package is able to simulate the evolution of ions, electrons, molecules and two different populations (or phases) of atoms in realistic 2D geometry. Simulations in ITER geometry show that, with a fluid breakdown parameter of up to 0.1÷0.5, only negligible differences are found with respect to fully-kinetic Soledge2D–Eirene cases, while at the same time improving the computational performances of the code package.